The dynamics of qualifications: defining and renewing occupational and educational standards - (:unkn) unknown (Office for Official Publications of the European Communities, 2009)
This report compares the use of qualifications standards in the 32 countries taking part in the "Education and training 2010" work programme. The report illustrates the diversity of approaches across Europe and underlines the importance of systematic dialogue between stakeholders to ensure the relevance and credibility of competences and qualifications. It includes in-depth case studies of five countries that have taken coordinated action to address national issues. The study pays particular attention to standards as bridges between education and training systems and the labour market. (BIBB-Doku)
Keywords: G 2.3.4 Qualifikationswandel; S 2.2.5 Standards in der beruflichen Bildung; I 2.1 Deutschland; I 2.2.1 Westeuropa; I 2.2 Europa; Berufsbildung; Berufliche Qualifikation; Bildungsstandards; Kompetenzstandards; Lernergebnisorientierung; Beziehung Bildungssystem Beschäftigungssystem; Fallstudie; Bundesrepublik Deutschland; Dänemark; Polen; Spanien; Vereinigtes Königreich; Europäische Union